The evaluation of the English textbook “Bahasa Inggris” for tenth graders of SMKN 7 Purworejo based on Paul Nation and John Macalister’s theory - Yan Imam Santoso (Universitas Sarjanawiyata Tamansiswa, 2021)
Abstract: Textbooks are the tools that should be available in teaching and learning. Textbooks are a set of teaching materials that are combined into books. No books are appropriate for all the characters of the students. the textbook for tenth graders is Bahasa Inggris. This book is recommended for senior high school and vocational school and is related to curriculum 2013. This research is focused on the evaluation of the textbook of Bahasa Inggris for tenth graders in SMK N 7 Purworejo according to the theory of Nation and Macalister. This research is aimed to discover the appropriateness or suitability of the textbook Bahasa Inggris for tenth graders in SMK N 7 Purworejo based on the Nation and Macalister theory and select the themes of the textbook that have been appropriate to the criteria. This research belongs to the descriptive qualitative research. In collecting the data, this research conducted a simple interview and document analysis. The findings of this research are the textbook is partly suitable for content analysis. Chapters 4 and 5 are partly suitable because the materials are not related to the needs. The teacher should modify the content. Chapters 12, 13 and 14 also need to be modified deeper. The format and presentation, monitor and assessment also have been suitable for the students of SMK N 7 Purworejo according to the theory of Nation and Macalister. When the themes of each chapter were compared to the criteria, the researcher found 12 appropriate chapters. Keywords: content and sequencing, evaluations, format and presentation, monitor and assessment, Nation and Macalister, textbooks.